A biofilm resistance surface yielded by grafting of antimicrobial peptides on stainless steel surface. (14th February 2018) - Cao, Pan; Yuan, Chengqing; Xiao, Jinfei; He, Xiaoyan; Bai, Xiuqin
Abstract : Anti‐biofilm formation on the surface is a severe issue in medical implants, hull surface, and food industry. Antimicrobial peptide, magainin II, was covalently bound to stainless steel surfaces through multi‐step modification. The untreated and modified samples were analyzed by SEM‐EDS, XPS, and contact angle, respectively, which indicated the peptide was immobilized on the surfaces. The antimicrobial tests of modified samples were conducted using Staphylococcus aureus and Escherichia coli, and the results revealed that peptide modified surface decreased the biofilm and bacteria quantity of stainless steel surface.